Differentiated Instruction Strategies to Enhance Critical Thinking Skills of Elementary Students in Cianjur Regency - Ai Nurhaeti; R. Supyan Sauri; Ifah Khadijah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study aims to analyze the contribution of differentiated instruction strategies in enhancing the critical thinking skills of elementary school students. Utilizing a qualitative approach with an intrinsic case study design, the research was conducted at SDN Jatinagara and SDN Bojongkadu, Cianjur Regency. The primary focus of the study encompasses three components of differentiated instruction: content, process, and product/assessment. Data collection techniques involved participatory observation, semi-structured interviews with teachers and students, and documentation of student assignments and critical thinking assessment rubrics. The results indicate that learning content tailored to students' readiness and interests increases engagement and explorative abilities. A learning process based on discussions and open-ended tasks encourages students to analyze, construct arguments, and evaluate alternative solutions. Assessments utilizing critical thinking rubrics and adaptive formats allow for a fair and valid evaluation of the thinking abilities of students from diverse backgrounds. Data triangulation strengthens the validity of the findings, and the calibration process among teachers demonstrates high reliability in applying the instruments. This study suggests strengthening teacher training and developing critical thinking evaluation systems in elementary schools based on differentiated instruction.